Comparison of Social Validity Ratings With the Effects of a Video-Feedback Intervention for Communication Partners of Individuals With Deafblindness - Damen, Saskia; Schuengel, Carlo; Ruijssenaars, Wied; Janssen, Marleen J. (Frontiers in Education, 2021)
The parents, teachers, and professional caregivers of individuals with disabilities may benefit from interventions to enhance their educational skills. The aim of the current study was to gain insight into the perceived relevance, feasibility, and effectiveness (i.e., social validity) of a video-feedback communication intervention for caregivers (i.e., parents, teachers, and professional caregivers) of individuals with congenital deafblindness. Responses on the Social Validity Scale from 25 caregivers who participated in the High-Quality Communication (HQC) intervention revealed that they considered the HQC intervention to be a relevant, feasible, and effective intervention. Comparing the caregiver ratings with previous effect studies on the HQC intervention at the individual case level, we found no association between the observed effectiveness of this intervention and caregivers’ opinions about its relevance and feasibility. The combination of observational and social validity data enabled a critical analysis of the clinical value of the HQC intervention. We recommend that future studies use multiple data source for social validity assessment.